2019
DOI: 10.1007/s40263-019-00692-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety and Efficacy of Blonanserin Transdermal Patches in Japanese Patients with Schizophrenia: A 52-Week Open-Label, Multicenter Study

Abstract: Background Blonanserin transdermal patch therapy is now available in Japan for the treatment of schizophrenia and may provide several advantages over the tablet formulation. Objective The aim was to evaluate the long-term safety and efficacy of blonanserin transdermal patches in Japanese patients with schizophrenia. Methods An open-label study was conducted in adults with schizophrenia at 37 sites in Japan. Patients were enrolled in either cohort 1 or 2. Patients in cohort 1 received 8-16 mg/day blonanserin ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…The peak occupancy of blonanserin tablets in this study was slightly higher than that of blonanserin patches, although satisfactory clinical effects were obtained in a placebo-controlled phase III study and 52-week long-term study of blonanserin patches at doses of 40 mg/d and 80 mg/d ( Iwata et al, 2020a , 2020b ). Lower peak occupancy in blonanserin patches compared with tablets may be attributed to maintenance of a certain level of both plasma blonanserin concentration and associated dopamine D 2 receptor occupancy.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The peak occupancy of blonanserin tablets in this study was slightly higher than that of blonanserin patches, although satisfactory clinical effects were obtained in a placebo-controlled phase III study and 52-week long-term study of blonanserin patches at doses of 40 mg/d and 80 mg/d ( Iwata et al, 2020a , 2020b ). Lower peak occupancy in blonanserin patches compared with tablets may be attributed to maintenance of a certain level of both plasma blonanserin concentration and associated dopamine D 2 receptor occupancy.…”
Section: Discussionmentioning
confidence: 54%
“…Importantly, there were no serious adverse events and no patients discontinued either treatment as a result of adverse events. Based on the present results and previous findings with oral blonanserin, target doses of 40 mg/d and 80 mg/d were established for a phase III study of blonanserin transdermal patches ( Iwata et al, 2020b ) and a study conducted to properly assess the long-term safety and efficacy of this formulation ( Iwata et al, 2020a ). Results of the phase III study found statistically significant decreases in the PANSS total score over 6 weeks, especially in the blonanserin 80-mg patch group, which was associated with a moderate effect size (0.555) vs placebo ( Iwata et al, 2020b ).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The 4 studies conducted in male and female patients with schizophrenia were (1) a positron emission tomography (PET) study for 2 weeks 9 (D4904019 [JapicCTI‐121914]); (2) a confirmatory study for 6 weeks 10 (D4904020 [NCT02287584, JapicCTI‐142688]); (3) a long‐term study for 52 weeks 11 (D4904040 [NCT02335658, JapicCTI‐152765]); and (4) a multiple application study for 2 weeks (D4904063 [JapicCTI‐142423]). The names and locations of study sites are listed in Table 1 and Table S1.…”
Section: Methodsmentioning
confidence: 99%